The trilogy of distance, speed and time - Banister, D (Elsevier, 2011)
Over the recent past there has been a dramatic increase in travel, mainly driven by the desire to move faster and over ever greater distances. This growth is unsustainable and the continued growth in levels of mobility needs to be reassessed through substantially reducing the levels of consumption (energy and carbon) in transport. This means that travel activities should be based on shorter distances and slower speeds, with a more flexible interpretation of time constraints. Transport geographers should have a strong and instrumental role to play in this debate. This paper outlines the changing patterns of movement, before concentrating on urban areas where most daily travel takes place and it examines the trilogy of distance, speed and time. The focus of the paper is on distance and the role that land use planning and development and technology can play in encouraging new forms of travel in cities, but there are strong implications on the ways in which speed and time are conceptualised. The conventional transport paradigm is heavily embedded in the belief that travel time needs to be minimised and consequently speeds need to be increased. The resulting impacts on travel distances have not been part of that debate, but reducing travel distances is central to sustainable transport.